Volatile sensation: The chemical ecology of the earthy odorant geosmin - Paolina Garbeva; Mariana Avalos; Dana Ulanova; Gilles P. van Wezel; Jeroen S. Dickschat (Environmental Microbiology, 2023)
Geosmin may be the most familiar volatile compound, as it lends the earthy smell to soil. The compound is a member of the largest family of natural products, the terpenoids. The broad distribution of geosmin among bacteria in both terrestrial and aquatic environments suggests that this compound has an important ecological function, for example, as a signal (attractant or repellent) or as a protective specialized metabolite against biotic and abiotic stresses. While geosmin is part of our everyday life, scientists still do not understand the exact biological function of this omnipresent natural product. This minireview summarizes the current general observations regarding geosmin in prokaryotes and introduces new insights into its biosynthesis and regulation, as well as its biological roles in terrestrial and aquatic environments.

Volatile‐mediated antagonism of soil bacterial communities against fungi - Xiaogang Li; Paolina Garbeva; Xiaojiao Liu; Paulien J. A. klein Gunnewiek; Anna Clocchiatti; Maria P. J. Hundscheid; Xingxiang Wang; Wietse de Boer (Environmental Microbiology, 2020)
Summary Competition is a major type of interaction between fungi and bacteria in soil and is also an important factor in suppression of plant diseases caused by soil‐borne fungal pathogens. There is increasing attention for the possible role of volatiles in competitive interactions between bacteria and fungi. However, knowledge on the actual role of bacterial volatiles in interactions with fungi within soil microbial communities is lacking. Here, we examined colonization of sterile agricultural soils by fungi and bacteria from non‐sterile soil inoculums during exposure to volatiles emitted by soil‐derived bacterial communities. We found that colonization of soil by fungi was negatively affected by exposure to volatiles emitted by bacterial communities whereas that of bacteria was barely changed. Furthermore, there were strong effects of bacterial community volatiles on the assembly of fungal soil colonizers. Identification of volatile composition produced by bacterial communities revealed several compounds with known fungistatic activity. Our results are the first to reveal a collective volatile‐mediated antagonism of soil bacteria against fungi. Given the better exploration abilities of filamentous fungi in unsaturated soils, this may be an important strategy for bacteria to defend occupied nutrient patches against invading fungi. Another implication of our research is that bacterial volatiles in soil atmospheres can have a major contribution to soil fungistasis.

Non‐random species loss in bacterial communities reduces antifungal volatile production - W. H. Gera Hol; Paolina Garbeva; Cornelis Hordijk; Maria P. J. Hundscheid; Paulien J. A. Klein Gunnewiek; Maaike van Agtmaal; Eiko E. Kuramae; Wietse de Boer (Ecology, 2015)
The contribution of low‐abundance microbial species to soil ecosystems is easily overlooked because there is considerable overlap between metabolic abilities (functional redundancy) of dominant and subordinate microbial species. Here we studied how loss of less abundant soil bacteria affected the production of antifungal volatiles, an important factor in the natural control of soil‐borne pathogenic fungi. We provide novel empirical evidence that the loss of soil bacterial species leads to a decline in the production of volatiles that suppress root pathogens. By using dilution‐to‐extinction for seven different soils we created bacterial communities with a decreasing number of species and grew them under carbon‐limited conditions. Communities with high bacterial species richness produced volatiles that strongly reduced the hyphal growth of the pathogen Fusarium oxysporum . For most soil origins loss of bacterial species resulted in loss of antifungal volatile production. Analysis of the volatiles revealed that several known antifungal compounds were only produced in the more diverse bacterial communities. Our results suggest that less abundant bacterial species play an important role in antifungal volatile production by soil bacterial communities and, consequently, in the natural suppression of soil‐borne pathogens.

Rhizosphere microbial community and its response to plant species and soil history - P. Garbeva; J. D. van Elsas; J. A. van Veen (Plant and Soil, 2008)

Effect of above‐ground plant species on soil microbial community structure and its impact on suppression of Rhizoctonia solani AG3 - P. Garbeva; J. Postma; J. A. Van Veen; J. D. Van Elsas (Environmental Microbiology, 2006)
Summary The extent of soil microbial diversity is seen to be critical to the maintenance of soil health and quality. Different agricultural practices are able to affect soil microbial diversity and thus the level of suppressiveness of plant diseases. In a 4‐year field experiment, we investigated the microbial diversity of soil under different agricultural regimes. We studied permanent grassland, grassland turned into arable land, long‐term arable land and arable land turned into grassland. The diversity of microbial communities was described by using cultivation‐based and cultivation‐independent methods. Both types of methods revealed differences in the diversities of soil microbial communities between different treatments. The treatments with higher above‐ground biodiversity generally maintained higher levels of microbial diversity. Moreover, a positive correlation between suppression of Rhizoctonia solani AG3 and microbial diversity was observed. Permanent (species‐rich) grassland and grassland turned into maize stimulated higher microbial diversities and higher levels of suppressiveness of R. solani AG3 compared with the long‐term arable land. Effects of agricultural practices on Bacillus and Pseudomonas communities were also observed and clear correlations between the levels of suppressiveness and the diversities of these bacterial groups were found. This study highlighted the importance of agricultural management regime for soil microbial community structure and diversity as well as the level of soil suppressiveness.